Additive manufacturing: shaping the future of the manufacturing industry – overview of trends, challenges and opportunities - D.E.P. Klenam; F. McBagonluri; T.K. Asumadu; S.A. Osafo; M.O. Bodunrin; L. Agyepong; E.D. Osei; D. Mornah; W.O. Soboyejo (Applications in Engineering Science)
Additive manufacturing (AM) is an innovative approach to the manufacturing mix globally. In this era of overwhelming complexities, tremendous competition and accelerated change, the increasing drive for rapid prototyping has necessitated the deployment of AM technologies and research. Three-dimensional (3D) modelling, 3D scanning and 3D printing have provided the impetus for design of functional and structural components at industrial scale. To contextualize the manufacturing landscape, an overview, and recent trends of conventional (subtractive) manufacturing technologies are discussed briefly. The challenges associated with these subtractive technologies in an increasingly resource constraint and exponential population growth paved the way for massification of AM approaches. Recent advances in AM technologies and applications in healthcare, construction, automotive and aerospace industries are discussed. The milestones, trends, opportunities, and challenges of AM technologies to the nascent technological landscape of Africa are also discussed. This review identifies AM as a pivotal enabler of Africa Union’s Agenda 2063, offering actionable pathways to overcome persistent challenges in industrial diversification, youth unemployment, and technological self-sufficiency. By leveraging localized AM applications and digital workflows, scalable solutions for sustainable development and manufacturing sovereignty can be realized with implications in leapfrogging the industrialization aspirations of Africa.